2013
DOI: 10.1007/s00508-013-0417-0
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate to long-term follow-up results of INH chemoprophylaxis prior to anti-TNF-alpha therapy in a high-risk area for tuberculosis

Abstract: TST is a reliable and cost-effective method for the diagnosis of LTBI in patients prior to anti-TNF therapy. Moreover, chemoprophylaxis with INH seems to be effective for the prevention of TB reactivation in individuals with LTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The TST is convenient, inexpensive, and easy to administer, rendering it a very efficient test for determining LTBI screening. Some studies detected no association between TST positivity and prior BCG vaccination, 21,22 although most studies indicated that TST was affected by previous BCG vaccination and immunosuppressive treatment 17,18,23 . As most of our patients were receiving immunosuppressive drugs before LTBI screening, it is likely possible to have false‐negative results with performing TST instead of the IGRA test for LTBI screening.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The TST is convenient, inexpensive, and easy to administer, rendering it a very efficient test for determining LTBI screening. Some studies detected no association between TST positivity and prior BCG vaccination, 21,22 although most studies indicated that TST was affected by previous BCG vaccination and immunosuppressive treatment 17,18,23 . As most of our patients were receiving immunosuppressive drugs before LTBI screening, it is likely possible to have false‐negative results with performing TST instead of the IGRA test for LTBI screening.…”
Section: Discussionmentioning
confidence: 87%
“…In a study conducted by Kurt et al 22 A diagnosis of LTBI was based on TST ≥5 mm in patients who were candidates for anti‐TNF treatment. TST was positive in 58 (79.4%) of 73 patients, including 50 (68.5%) with BCG vaccination who were treated with anti‐TNF agents for the rheumatological disease, and none of the patients (0%) developed signs of TB during 24 months of follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study with rheumatic diseases of 86 patients, chemoprophylaxis has been given 58 cases for 9 months and TB disease was not detected at the two month follow up [29]. In our study, we followed up 2 of 110 patients (1.8%).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, the rate of tuberculosis development was reported as 0.85% by Çağatay et al, and 1.5% by Hanta et al(18,19). Contrary to these studies, Girit et al and Kurt et al reported that tuberculosis did not develop in any of the patients receiving anti-TNF (14,20). Con icting results have been reported in studies examining the bene t of prophylaxis for LTBI.…”
Section: Discussionmentioning
confidence: 92%